Risk factors associated with carcinoma breast: a case control study - A., Palachandra; D., Ishwaraprasad G.; Y., Sreelatha C.; M., Sumana (International Surgery Journal, 2017)
Background: The burden of breast cancer is increasing in both developed and developing countries; the peak occurrence of breast cancer in developed countries is above the age of 50 whereas in India it is above the age of 40. Reproductive factors contribute most to the development of breast cancer. Nulliparity, more age at first live birth and no breastfeeding are major reproductive risk factors for breast cancer in the developed countries. The role of reproductive factors in the development of breast cancer in Indian population is different as compared with that seen in the western population. Objective of this study was to find out some of the various risk factors of breast cancer among patients attending the tertiary care hospital in Hassan. Methods: The case control study was conducted at surgery wards of Sri Chamarajendra district hospital which is a teaching hospital. The calculated number of cases was 110, including 110 controls total 220 individuals were included in the study. A case was defined as any female patient histopathologically confirmed to have breast cancer. Results: The maximum cases (38%) were between 51 to 60 years of age group. Age at menarche, age at first child birth, age at marriage and age at menopause reported significant risk for breast cancer. Conclusions: Information, education and communication activities regarding these risk factors, early signs and symptoms of breast carcinoma, and breast self‑examination should be imparted to the women to create awareness about this fatal disease.